Particle Detection with Drift Chambers - Blum, Walter; Riegler, Werner; Rolandi, Luigi (Particle Acceleration and Detection,, 2008)
This volume presents a thorough introduction to the theory and operation of drift chambers, one of the most important modern methods of elementary particle detection. The topics, presented in a text-book style with many illustrations, include the basics of gas ionization, by particles and by lasers, drift of electrons and ions in gases and signal creation and discuss in depth the fundamental limits of accuracy and the issue of particle identification. The book also surveys all types of drift chambers and the various drift-chamber gases in use. The calculation of the device parameters and physical processes are presented in some detail, as is all necessary background material. Thus the treatment, well beyond addressing the specialist in the field, is well suited to graduate physics students and nuclear engineers seeking a both thorough and pedagogical introduction to the field. The second edition presents a completely revised, updated and expanded version of this classic text. In particular, significantly more material on electronic signal creation, amplification and shaping has been added.